HIV Serostatus Disclosure to Sexual Partners Among People Living with HIV (PLWHA) in Southwest Nigeria - Gbemiga Peter Olubayo, Saheed Opeyemi Usman *, Funmilola Olive Abodunde (Sokoto Journal of Medical Laboratory Science)
Disclosure of HIV sero-status especially to sexual partners carry high potential to increase uptake of HIV testing and counselling, antiretroviral therapy and treatment outcomes among People Living with HIV/AIDS (PLWHA). Nigeria has the second highest number of PLWHA globally following South Africa. However, available studies revealed a low disclosure rate of HIV sero-status among the general population. In view of this, there is a need to understand the barriers to disclosure and document its implication especially in achieving the last 90 in the UNAIDS 90-90-90 target by year 2020. This descriptive cross-sectional study was conducted among 501 consenting HIV positive patients randomly selected from six adult antiretroviral clinics in Ondo and Ekiti States, South-West Nigeria. The questionnaire was reviewed by three experts to ascertain face validity while pilot study was conducted with adequate internal consistency (Cronbach’s alpha = 0.75). Data were collected by trained volunteers who were calibrated before the field study. All data were analyzed, using Statistical Package for Social Sciences (SPSS) and statistical test of significance was performed with Chi-Square test. The mean age of respondents was 39.05 ± 9.48 years. A total of 154 (30.7%) subjects are males while 347 (69.3%) are females. Among the subjects studied, only 334 (66.7%) have disclosed their HIV status of which 92.5% were to main partners only.  Among those that disclosed, 299 (89.5%) of disclosure happened within the first three months of diagnosis. Fear of stigma and discrimination, and fear of divorce are largely responsible for most (78.2%) non-disclosure. Level of education did not affect HIV status disclosure (χ² = 10.949, df = 6, p = 0.090). Subjects who disclosed to their family members are more likely to disclose to their sexual partner (OR: 1.98, 95% CI: 1.35-2.90) while those who disclosed their HIV status to their sexual partners were four times more likely to achieved virological suppression (OR: 4.13, 95% CI: 2.40 -7.09). The study revealed a close linkage between HIV sero-status disclosure and patient treatment outcome. In order to optimize all the benefits linked with status disclosure, stigma and discrimination probable elimination programmes through multi-faceted community approach geared towards creating an enabling environment for HIV sero-status disclosure are needed.